Prevalence of Methicillin Resistant Staphylococcus Aureus In Khwaja Yunus Ali Medical College Hospital (KYAMC Journal, 2017)
Background: Methicillin-resistant Staphylococcus aureus (MRSA) is a major cause of healthcare-associated infections. To combat the challenge of life threatening MRSA remains a primary focus of most hospital infection control programs6. This study is undertaken in Khwaja Yunus Ali Medical College Hospital to identify the MRSA for determination of its prevalence and is considered a component of an infection control program in many countries5.Methods: Three hundred seventy hospitalized patients of surgery and medicine departments were studied during 2015. Clinical information of the patients and their pus, wound swab, sputum, throat swab and CSF were cultured.Results: Out of 370 patients, pus and wound swab of 217 (59%) had wound infection, sputum and throat swab of 141 had respiratory tract infection (38%) and CSF of 12 (3.2%) had meningitis were aseptically collected and cultured. Staphylococcus aureus were isolated in 51% cases and out of them MRSA was identified in 72 (73%) cases. MRSA isolated in 50% cases of meningitis, 49% cases of respiratory tract infection and 29% cases of wound infection.Conclusion: Methicillin-resistant Staphylococcus aureus appeared as a common cause of major illness and death and impose serious economic costs on patients and hospitals of our area like other developing countries. Detection of MRSA was associated with more severe clinical presentation.KYAMC Journal Vol. 7, No.-1, Jul 2016, Page 673-677